Facilities and Infrastructure Governance in Supporting Service Performance at the Department of Manpower, Cooperatives, and SMEs of North Minahasa Regency - Demsi Y. Lempas; Goinpeace H. Tumbel; Steven V. Tarore (JR Education, 2026)
This article develops a journal-style synthesis of Demsi Yohan Lempas's thesis on facilities and infrastructure governance in supporting service performance at the Department of Manpower, Cooperatives, and SMEs of North Minahasa Regency. The study addresses a practical problem in local public administration: regional apparatus organizations are required to deliver faster, more accountable, and increasingly digital services, yet many of the physical and technological assets that support those services remain insufficient, damaged, or administratively managed rather than strategically optimized. Using a qualitative descriptive design, the original thesis collected data through interviews, observation, and documentation involving officials of the department and related asset management actors. This article reorganizes the thesis into an academic journal format modeled after the Sammy IJITE article, while preserving the empirical core of the thesis. The findings show that Regional Government Asset (Barang Milik Daerah/BMD) management has been implemented through planning, procurement, utilization, maintenance, and administration, but it has not yet reached an optimal level. Planning is still not fully based on real service needs, procurement is constrained by budget limitations, utilization is affected by damaged and idle assets, maintenance remains reactive, and administration is weakened by data inconsistency and limited digital integration. The most important inhibiting factors are limited human resources, insufficient budget, inadequate facilities and infrastructure, and weak integrated management systems. The article argues that facilities and infrastructure should not be treated as passive office equipment, but as strategic service capacity. Strengthening requires needs-based planning, priority-based budgeting, preventive maintenance, digital inventory, improved human resource capacity, and service-oriented monitoring. The study contributes to public administration literature by showing how asset governance directly shapes local service performance in the fields of employment, cooperatives, and SME development.